2015
DOI: 10.1039/c4an02121e
|View full text |Cite
|
Sign up to set email alerts
|

Analyte induced water adsorbability in gas phase biosensors: the influence of ethinylestradiol on the water binding protein capacity

Abstract: An ultra-sensitive gas phase biosensor/tracer/bio-sniffer is an emerging technology platform designed to provide real-time information on air-borne analytes, or those in liquids, through classical headspace analysis. The desired bio-sniffer measures gaseous 17α- ethinylestradiol (ETED) as frequency changes on a quartz crystal microbalance (QCM), which is a result of the interactions of liquid sample components in the headspace (ETED and water) with a biorecognition layer. The latter was constructed by immobili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…This effect of small doses has been observed many times in various physical, chemical and biological systems. [30][31][32][33] A similar effect was noted by the authors of the work, 34 where with an increase in the copper concentration during the synthesis of zinc oxide, the intensity of the diffraction peak of the dominant texture (002) first increased and then decreased.…”
Section: Introductionsupporting
confidence: 73%
“…This effect of small doses has been observed many times in various physical, chemical and biological systems. [30][31][32][33] A similar effect was noted by the authors of the work, 34 where with an increase in the copper concentration during the synthesis of zinc oxide, the intensity of the diffraction peak of the dominant texture (002) first increased and then decreased.…”
Section: Introductionsupporting
confidence: 73%
“…At the same time the effects of analyte induced water adsorbtion may be used for design and development of unique ultrasensitive approaches with detection limit up to 10 −17 g/L of potent xenobiotics (see 7.2, [51]). …”
Section: Humiditymentioning
confidence: 99%
“…To illustrate, it was shown that the variations in the QCM response are due to the change of water-binding capacity of the biorecognition layer induced by protein transformations initiated by the binding of ethinylestradiol molecules [51].…”
Section: Structural Reorganization In Sensing Surface Architecture Inmentioning
confidence: 99%
“…However, modern chemistry is still unable to predict and synthesize chemical structures with precisely tuned chemical functionality. This explains the fact that an increasing number of researchers are testing the molecular biosystems of living organisms with their predetermined functionality as sensitive layers of sensors [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…As with other albumins, OVA binds well to a wide variety of substances, including those that are poorly soluble in water; the adsorption capacity can reach more than 10% of the protein weight. Such features of albumins allow us to consider their coatings as promising sensitive layers in gaseous biosensors (so-called "bio-sniffers" [1,2,5,6]). In this work, we study the possibility for OVA layers deposited on different substrates (namely, silver, silver coated by buckminsterfullerene C 60 , and silver coated by copper phthalocyanine CuPc) to be a sensitive coating in QCM transducers to detect various analytes such as water, alcohols, acetone, cyclohexane, and benzene.…”
Section: Introductionmentioning
confidence: 99%